INTELLECTUAL PROPERTY RELATED TO TRADITIONAL AND MODERN AGRICULTURE IN SERBIA - Jovanović, Slobodanka; Sikora, Sonja; Petrović, Slobodan (Economics of Agriculture, 2012)
Agricultural progress has been the most important factor which leads to humans civilization. The world has progressed in such a rapid manner that traditional agriculture has aggressively been replaced by modern agricultural approaches and methods. Traditional knowledge and innovations relating to food and agriculture are widespread, viable and sustainable. The subject matter of protection traditional knowledge may include agricultural, environmental and knowledge associated with genetic resources. Protection of the traditional knowledge and results of the modern agriculture, under existing models of intellectual property rights could involve: copyrights, patents, plant varieties, trademarks, geographical indications and appellations of origin. While patents protect new and inventive products and processes, geographical indications protect traditional knowledge and skills associated with certain products which are typically passed down through generations, and have a strong link with the underlying geographical territory.